Efficacy of Oral Nicorandil to Prevent Contrast-Induced Nephropathy in Patients with Chronic Renal Dysfunction Undergoing an Elective Coronary Procedure - Zeyuan Fan; Yang Li; Hanhua Ji; Xinwen Jian (Karger Publishers, 2019)
Objectives: This prospective, randomized study was to investigate the role of nicorandil in the prevention of contrast-induced nephropathy (CIN) in patients with chronic renal dysfunction undergoing an elective coronary procedure. Methods: A total of 252 eligible patients were enrolled in this study and allocated into the control group (n = 125) or nicorandil group (n = 127). Both groups received the standard hydration treatment, and patients in the nicorandil group were orally administrated 10 mg of nicorandil (t.i.d.) beginning 2 days before and continuing for 2 days after an elective coronary procedure. Serum creatinine (SCr) and cystatin C (CysC) were measured at 24 h before and 24, 48, and 72 h after the procedure. The occurrences of CIN and adverse events within 1 year were recorded. Results: The nicorandil group had relatively lower SCr and CysC levels and a higher eGFR at 24 and 48 h after the procedure than the control group (p < 0.05). The incidence of CIN was significantly decreased in the nicorandil group compared to the control group. The multivariate logistic regression model revealed that nicorandil treatment was an independent protective factor for CIN (OR 0.669, 95% CI 0.522-0.857, p = 0.001). The multivariate COX proportional hazard model showed that nicorandil treatment was an independent protective predictor for adverse events (HR 0.881, 95% CI 0.781-0.993, p = 0.037). Conclusions: Nicorandil could exhibit a protective effect against CIN in patients with chronic renal dysfunction undergoing an elective coronary procedure and reduce the adverse events within 1 year after the procedure, which is superior to hydration treatment only.